Relative Importance of Political Instability and Economic Variables on Perceived Country Creditworthiness - Lee, Suk Hun (Journal of International Business Studies, 1993)
This paper examines the relative importance of political instability and economic variables on perceived country creditworthiness. Our results indicate that both political instability and economic variables are taken into account in evaluating country creditworthiness; however, it appears that bankers assign larger weight to economic variables. Hence, it seems that the country creditworthiness perceptions are largely based on a country's economic performances, which we except to reflect longer term political stability. In addition, the frequency of changes in the regime and armed conflict, both proxying for political instability, also affect the credit ratings.